Specifika religioznoj tolerantnosti v Kazachstane - Sabitkyzy, A. (Chabaršy. Dintanu serijasy, 2023)
The modern world is becoming more conflictual, and interethnic, interreligious contradictions and problems at the international and regional levels are even more aggravated. Western politicians and public figures talk about the collapse of multiculturalism, and anti-immigrant sentiments in Europe, caused by powerful migration pressure on Western society and manifestations of terrorism, have raised the question of the crisis of tolerance in the world. Even in developed democratic countries, manifestations of nationalism, chauvinism and aggression in inter-ethnic, inter-racial, inter-confessional and other relations are spreading. After gaining independence, the Republic of Kazakhstan entered a new historical stage of development characterized by deep political transformations against the background of the rise of national and religious self-consciousness in the conditions of multi-ethnicity of the society, formed during the Soviet period, and multiconfessionality, formed in the course of democratic transformations. During the transformation of the economic and political system of Kazakhstan there are many potential risks, which under certain conditions can be realized and have a negative impact on the stability of society. In today's globalizing world, the principle of tolerance is the most important principle of interethnic harmony and is one of the elements of fundamental interpersonal ethics, in which absolutely every human being is thought of as a socially superior being, and nothing has the right to deny his cultural and social identification if it leads to the prosperity of society on a global, planetary scale.